P185 Psychosocial impact of the COVID-19 pandemic on patients with inflammatory bowel disease in Spain. (27th May 2021) - Hernandez Camba, A; Ramos, L; Madrid Álvarez, M B; Pérez-Méndez, L; Nos, P; Hernández, V; Guerra, I; Jimenez, N; Lorente, R; Sierra-Ausín, M; Ginard, D; Varela, P; et al.
Abstract: Background: Few studies have examined the effects of COVID-19 on the mental health of patients with inflammatory bowel disease (IBD), who are already at higher risk of depression, anxiety and stress than the general population. This cross-sectional study was conducted to assess the psychosocial impact of COVID-19 on patients with IBD in Spain during lockdown and the first wave of the pandemic. Methods: A self-report questionnaire that integrated the Spanish version of the Depression, Anxiety and Stress Scale–21 items (DASS-21) and the Perceived Stress Questionnaire (PSS) was designed to gather sociodemographic data and information related to the effects of COVID-19 on the lives of IBD patients. Twelve IBD units invited their patients to answer the anonymous online survey via email or by using a QR code displayed at the unit. A link to the survey was also published on the GETECCU (Spanish IBD group) website and social media account. The survey was conducted between the 1 st July and the 25 th August 2020. Results: Of the 693 survey participants with IBD, 67% were female, mean age 43 (12y SD). 61% had ulcerative colitis, 36% Crohn's disease 3% indeterminate colitis. Only 15 participants were diagnosed with COVID-19: 3 of them required hospital admission and none required ICU admission. Physical activity levels and sleep habits were adversely affected for 79% and 67% of respondents, respectively. In addition, 39% reported a decrease in income due to the pandemic. 95% report having complied with IBD treatment during the COVID-19 pandemic, despite over 50% of them feeling that they were more at risk of infection due to their medication. DASS-21 scores indicate that during the lockdown the estimated prevalence of depression was 10.5% [95% CI 8.2–13%], anxiety 20% [95% CI –17–23%] and stress 18% [95% CI 8.2–13%]. Multivariate analysis is described in table 1. Conclusion: In the short-term, lockdown during the COVID-19 pandemic seemed to have an impact on the mental health of our IBD patients in Spain. Further follow-up studies should be carried out to determine the real long-term impact, as it's known that the wellbeing of this population might be affected because of IBD itself.